1986
DOI: 10.1515/znb-1986-1208
|View full text |Cite
|
Sign up to set email alerts
|

On the Autoxidation of Aqueous Sodium Polysulfide [1]

Abstract: AbstractAqueous sodium polysulfide of composition in the range Na2S2.0 to Na2S4.6 undergoes autoxidation by either air or pure oxygen at temperatures of between 23 and 40 °C according to the equation [xxx]Iodometric determination, vibrational spectra and ion-pair chromatography showed that neither sulfate, sulfite nor polythionates are formed and that the sulfur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 0 publications
0
33
0
Order By: Relevance
“…Notably, marked accumulation of glutathione occurred in tomato cells carrying resistance genes in response to specific fungal elicitors (May et al, 1996). Localized accumulation of glutathione and subsequent degradation together with chemical oxidative processes (Steudel et al, 1986) could result in the observed depositions. Future work will focus on the identification of Cys degradation pathways, for example the identification of a Cys desulfhydrase (Schmidt, 1987).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Notably, marked accumulation of glutathione occurred in tomato cells carrying resistance genes in response to specific fungal elicitors (May et al, 1996). Localized accumulation of glutathione and subsequent degradation together with chemical oxidative processes (Steudel et al, 1986) could result in the observed depositions. Future work will focus on the identification of Cys degradation pathways, for example the identification of a Cys desulfhydrase (Schmidt, 1987).…”
Section: Discussionmentioning
confidence: 98%
“…The origin of the elemental S production in plants may be from glutathione or Cys degradation, possibly via the action of an, as yet uncharacterized, Cys desulfhydrase (Rennenberg et al, 1987;Schmidt, 1987). It is possible that sulfide is a by-product of the degradation of these thiols and it is this sulfide that is oxidized to form elemental S in a non-enzymic reaction (Steudel et al, 1986).…”
mentioning
confidence: 99%
“…Though the maximum chain length of polysulfides present in yellow to orange solutions is uncertain, most observations suggest coexistence of species with up to six sulfur atoms [11,13]. Consequently, the separation of individual polysulfides is not an easy task.…”
Section: Introductionmentioning
confidence: 99%
“…The well-known reactivity of sulfur species (27,28) suggests caution in the interpretation of our results; we cannot entirely rule out the possibility that the experimental conditions used for analyses would promote the oxidation of polysulfide, polythionates or HS-to elemental sulfur (27,28 …”
Section: Resultsmentioning
confidence: 94%